Incidental lung findings in a COVID-19 patient on 18F-FDG PET/CT done for preoperative evaluation of Marjolin's ulcer-first report from Chhattisgarh - Ravina, Mudalsha; Baruah, Tridip Dutta; Lukose, Tinu; Ganga, Ranganath T.; Moideen, Amal (World Journal of Nuclear Medicine, 2021)
The aim of this case is to illustrate the 18F-fluorodeoxyglucose (FDG) positron emission tomography-computed tomography findings of a patient who was admitted in AIIMS, Raipur, for the preoperative evaluation of Marjolin ulcer and was later diagnosed with COVID-19 infection. Apart from the primary lesion in the right foot and pelvic lymph nodes, the scan revealed mild FDG-avid basal ground-glass opacities in bilateral lung fields with mediastinal and hilar lymph nodal involvement, in an otherwise asymptomatic patient.
Keywords: Asymptomatic; coronavirus; COVID-19; fluorodeoxyglucose positron emission tomography-computed tomography; ground-glass opacification; mediastinal lymph nodes